Critical Thinking Ability in a STEM-Based Problem-Based Learning Model: A Focus on Temperature and Heat - Ekasari, Aprilita; Algiranto, Algiranto (Universitas Lambung Mangkurat, 2025)
This study explores enhancing students' critical thinking skills by applying a STEM-centered problem-based learning (PBL-STEM) model. It evaluates students’ responses to this pedagogical approach. A quasi-experimental design with a static group pretest-posttest framework was employed, involving secondary school students from Merauke City. The instrument used for data collection was a Critical Thinking Ability Test, which included 10 essay questions covering six subtopics related to temperature and heat and incorporated five indicators of critical thinking. The test's reliability, as measured by Cronbach's alpha, was 0.739. Additionally, student responses to the PBL-STEM method were gathered through questionnaires. Data were analyzed both descriptively and inferentially. The results indicated that implementing PBL-STEM was effective, significantly improving students' critical thinking skills, with an N-gain of 0.824, classified as high. Furthermore, the significance test revealed that the enhancement in critical thinking through PBL-STEM was greater than that achieved through traditional PBL methods.